Afforestation in the 'Kholas' of Hastinapur (Meerut) - Srivastava, R. L. (Indian Forester, 1953)
In collaboration with Colonization Department, the Forest Department, U.P. has recently undertaken reforestation of Ganga "Kholas" in Meerut District. Natural cover has so far been inhibited by biotic agencies with the result that the conditions have deteriorated and retrogression set in. Soil wash-off and formation of ravines has been very active. This article provides the general history and the technique involved in the control of erosion by raising large scale plantation.